Reorientacja priorytetów rozwojowych euroregionu Nysa (ERN) po przystąpieniu Polski i Czech do Unii Europejskiej - Adamczuk, Franciszek (Reversal of Development Priorities in Euroregion Nysa (ERN) after Poland's and Czech Republic's Accession to European Union, 2006)
The article is about development priorities in Polish, German and Czech Republic part of Euroregion NYSA. Author discusses the realization and effects of these priorities between 1994 and 2005 seen in the context of the first concept of development in Euroregion NYSA which was created in Germany in 1993. The author also wanted to show development priorities for Euroregion NYSA after access Poland's and Czech Republic's accession to the European Union. The article is based on a survey which was made between 2004 and 2005 by Polish, German and Czech researchers which cooperated with the author of the article. The survey shows consequences of the enlargement of the European Union and development of Euroregion NYSA.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 65-74